Aplicación de las herramientas de la ingeniería de métodos en el cultivo de arroz para incrementar la rentabilidad en las empresas agrícolas del Valle Jequetepeque - Cabanillas Tejada, Jersonn (2020)
The objective of this project is to diagnose, study, formulate and implement method engineering in rice cultivation in a sample of agricultural companies in the Jequetepeque Valley to increase profitability, with funding from the National Institution of Agricultural Innovation through the National Program of Agrarian Innovation, being key piece the volume of the hydric resource that is used for all the process of this crop, to reduce and to save its consumption. In the first instance through interviews and the observation of the cultivation of other plots, it is possible to identify the main problems and difficulties for both the farmer and the worker, which was used to draw up an Ishikawa diagram, as well as to define the detailed of activities of the whole process rice cultivation, in the stages of preparation of land and nursery, the activities are shared receiving the same treatment for both plots that will be treated until the transplant in final the field where from that moment they will be carried out under different methods of irrigation : the traditional method of irrigation of constant sheets of water and the method of irrigation of intermittent dry. In both methodologies, it is elaborated diagrams to standardize the processes, besides the measurement of standard times by activity, evaluation of pests, in the activity of harvest is elaborated a man-machine diagram to evaluate efficiency, besides comparisons between indicators of productivity, efficiency and profitability in the process of rice cultivation, as well as in the process of milling. Obtaining as a result in sowing and cultivation that the cost of producing a kilo of rice has a difference of S / .0.16 and per sack bag of 70 kg, of S / .11.06 in favor of the plot through the treatment of intermittent irrigation, being its profitability of 32.09%, while in the irrigation of constant sheets is 15.26% profitable. Additional in the process of milling, the rice obtained from the process of the cultivation under the intermittent irrigation presents an efficiency of 66.14%, a cost of S / 1.91 per kilogram piled and S / .93.41 per bag of 49 kilograms, and a profitability of 29.20%, regarding the product obtained by the cultivation under the traditional irrigation of constant sheets, an efficiency of 65.27%, S / .2.19 per kilogram, S / .107.07 per bag and its profitability of 13.22%, as a result generating a margin of greatest utility to the agricultural enterprise..